An Evaluation on Türkiye-Paraguay Diplomatic and Commercial Relations - İncesu, Ali Caner (Cappadocia Journal of Area Studies, 2024)
Within the scope of the Latin American Action Plan launched by the Republic of Türkiye in 2006, diplomatic relations with Latin American countries were reviewed. Paraguay, which is a part of the aforementioned opening up policies, is a country that tends to strengthen its relations with Türkiye. For Paraguay, which is among the developing countries of Latin America, Türkiye is an important gateway to the Middle East and a strategic partner. Considering the general sympathy towards Turks in South America and the fact that no negative incident has ever occurred in the history of Türkiye-Paraguay diplomatic relations, Paraguay is believed to be among Türkiye’s allies in South America. Paraguay, a member of the South American Common Market (MERCOSUR), is an important destination for Turkish businesspeople and entrepreneurs with new opportunities. It is also considered to be a new raw material market. Although positive diplomatic developments have been observed between the two countries in recent years, it is understood that this positive atmosphere has not led to a serious acceleration in Türkiye-Paraguay trade relations. The study concludes that Turkish businesspeople and entrepreneurs should pay more attention to Paraguay’s commercial potential and that Türkiye should emphasize more its policies in Paraguay and the South American region.